Dataset "Analytical modelling for prediction and prevention of overflow occurrence in wire-based additive manufacturing" - Haghighi, Alireza M.; Ding, Jialuo; Sun, Yongle (Cranfield University, 2026)
Wire-based directed energy deposition (w-DED) is an emerging additive manufacturing technology that has great potential for more efficient building of large-scale metallic structural components. Increasing the deposition rate is one of the primary goals to meet the low-cost demand for large-scale parts. However, a high deposition rate usually requires higher heat input to fully melt the material, which could lead to overflow defects. The occurrence of overflow can be attributed to those factors which interfere with the balance between gravitational and surface tension forces acting on the molten material. This disruption reduces the melt pool stability and imbalance the forces, ultimately generating overflow defects in the deposited layer. This paper presents a thermo-capillary-gravity model for predicting the overflow occurrence based on a criterion of the analytically calculated reciprocal Bond number, V80. Experiments show that if the 1/B0 is no greater than 0.74 or the bead height is no less than 1.16 times the capillary length, there will be a high probability of overflow occurrence. Two w-DED processes using mild steel and duplex stainless-steel wires were employed to validate the model, demonstrating an overall average accuracy of 84% and 93%, respectively. It is also found that both energy and material feed rates, which are two generic physical factors, significantly affect the molten material overflow. The validated modelling approach enables efficient prediction and control of overflow for high-quality high deposition rate w-DED processes.
Keywords: Directed Energy Deposition; Wire Arc Additive Manufacturing; Analytical Model; Overflow Prediction